2013
DOI: 10.1007/s40264-013-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Adverse Events Among Healthcare Workers Following H1N1 Mass Immunization in Ghana

Abstract: The most prominent adverse events reported were headaches, dizziness, muscle and joint aches, weakness, fever and injection-site pain. Although similar events were reported in other studies, the incidence was different and there were a few differences in the most frequently reported events. More studies of a similar nature should be encouraged in low- and medium-income countries to bridge the information gap with the developed world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Similar observations have been described with other vaccines. [7][8][9][10] The other signs and symptoms reported in this study were found to be similar to those described elsewhere with other vaccines. [8][9][10] No case of AEFI associated with OPV in adult population and in the pediatric population could be found with the use of available computer-assisted medical literature search programs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar observations have been described with other vaccines. [7][8][9][10] The other signs and symptoms reported in this study were found to be similar to those described elsewhere with other vaccines. [8][9][10] No case of AEFI associated with OPV in adult population and in the pediatric population could be found with the use of available computer-assisted medical literature search programs.…”
Section: Discussionsupporting
confidence: 83%
“…[7][8][9][10] The other signs and symptoms reported in this study were found to be similar to those described elsewhere with other vaccines. [8][9][10] No case of AEFI associated with OPV in adult population and in the pediatric population could be found with the use of available computer-assisted medical literature search programs. However, according to a WHO document entitled 'supplementary information on vaccine safety, background rates of adverse events following immunization', 11 common minor vaccine reaction associated with OPV are fever, irritability, malaise, and non-specific symptoms, such as diarrhea, headache, and/or muscle pain.…”
Section: Discussionsupporting
confidence: 82%
“…4,7,8 Smartphone penetration in Australia was reported at 65% in 2013, making it a suitable market for the use of such technology. 8 In the same survey, smartphone use is reportedly less common in other countries such as the United Kingdom (62%) and the United States (56%), however overall there is increasing smartphone penetration globally, and in future the use of this technology has applications any time a new vaccine is introduced.…”
Section: Resultsmentioning
confidence: 99%
“…There was one study on Haemophilus influenza type b vaccine 28 , two studies on influenza A (H1N1) vaccine 29,30 , one study on measles-rubella vaccine 31 , one study on meningococcal vaccine 32 , one study on oral polio vaccine 33 , two studies on pneumococcal vaccine 34,35 , one study on rotavirus vaccine 36 , two BCG vaccine studies 37,38 and one yellow fever vaccine study 39 . With the exception of only one study which assessed two vaccines (Measles-Rubella) in one formulation 31 , all the remaining studies assessed vaccines containing only one active ingredient.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…West, East, Central, North and Southern Africa were represented. The West African countries were Ghana 29,36 , Togo 39 , Benin 39 , Mali 32,36,39 , Senegal 32,39 , Liberia 39 , Guinea 39 , Sierra Leone 39 and Gambia 32,34 . The east African country was Kenya 39 .…”
Section: Identificationmentioning
confidence: 99%